2011
DOI: 10.1016/j.bbmt.2011.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anti-HLA Antibodies in Hematopoietic Stem Cell Transplantation

Abstract: Donor-specific antihuman leukocyte antigen antibodies (DSHA) have been clearly implicated in graft rejection in solid organ transplantation. Their role in allogeneic hematopoietic stem-cell transplantation (allo-HSCT) remains unclear. We summarize here evidence supporting a role for DSHA in graft failure in animal models of allo-HSCT and in clinical settings whenever no full HLA matching occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…However, DSA, a phenomenon not encountered with fully HLAmatched donors, increases the risk of graft failure [10]. Additionally, DSA only detectable by highly sensitive immunoassays also significantly increases the risk of graft failure [12-16,24]. Although the adverse impact of DSA on alloBMT outcomes is well recognized, their overall incidence is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, DSA, a phenomenon not encountered with fully HLAmatched donors, increases the risk of graft failure [10]. Additionally, DSA only detectable by highly sensitive immunoassays also significantly increases the risk of graft failure [12-16,24]. Although the adverse impact of DSA on alloBMT outcomes is well recognized, their overall incidence is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ciurea et al [41] found that DSHAs were associated with a high rate of graft rejection in patients undergoing haploidentical HSCT. On the basis of the previously mentioned findings, DSHA identification should be performed in HSCT settings where HLA matching is not complete [42]. Immunoadsorption and plasmapheresis could be considered to desensitize the recipient when no alternative donor is available.…”
Section: The Role Of Anti-hla Antibodiesmentioning
confidence: 99%
“…Besides factors such as age, sex, disease stage, conditioning regimen and degree of HLA identity that can affect the outcomes of allo-HSCT, anti-HLA antibodies, especially donor-specific anti-HLA antibodies (DSHAs), have been shown to have a negative prognostic impact in patients who undergo cord blood transplantation (CBT) [2], haploidentical SCT [3], and HLA-mismatched unrelated SCT [4]. Having anti-HLA antibodies or DSHAs have a negative effect on engraftment and contributes to a lower overall survival (OS) rate and higher graft failure [5][6][7]. The National Marrow Donor Program (NMDP) and the Center for International Blood and Marrow Transplant Research (CIBMTR) provide guidelines in 2012, in which anti-HLA antibody and HLA-DP loci typing should be examined as a part of the pre-transplantation work-up for unrelated adult donor and cord blood graft selection [8].…”
Section: Introductionmentioning
confidence: 99%